Analisis Relevansi Pertumbuhan Penduduk Terhadap Kesejahteraan Masyarakat Dengan Pendapatan Sebagai Variabel Intervening Di Kecamatan Angkola Barat - Pane, Pertama Yul Asmara; Patriansyah, Wawan; Ramadhona, Elfi Syahri (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the relevance of population growth to community welfare in Angkola Barat District, with income as an intervening variable. The continuously increasing population growth potentially affects the level of community welfare, both directly and indirectly through income. This study uses a quantitative approach with path analysis methods to determine the direct and indirect relationships between variables. Primary data was obtained through the distribution of questionnaires to 100 respondents selected purposively, while secondary data was obtained from relevant institutions. The results of the study show that population growth has a direct negative effect on community welfare. However, when mediated by the income variable, the effect becomes insignificant. These findings indicate that income increases have not been able to offset the negative impact of population growth on welfare. Therefore, policies are needed that not only control the rate of population growth but also encourage increased economic productivity of the community so that income can truly have a positive impact on welfare. This research contributes to regional development planning that is oriented towards sustainable welfare.